Pregnancy in breast cancer survivor with anthracycline induced cardiomyopathy - Prasad, Madhva; Chamariya, Sumit; Khadkikar, Rashmi; Chauhan, Anahita (International Journal of Research in Medical Sciences, 2017)
With earlier diagnosis and improved treatment modalities and management of breast cancer patients, survival is improving. An increasing number of survivors are in the reproductive age group; however a neglected medical area is contraceptive advice, failure of which can result in unwanted pregnancy and further medical complications. An undiagnosed pregnancy in a breast cancer survivor with known anthracycline- induced cardiomyopathy is presented here.